ANALISIS PAJAK PERTAMBAHAN NILAI DAN PAJAK PENGHASILAN PASAL 22 PADA PT. MAKMUR AUTO MANDIRI - Bala, Gladys Mita Marthina; Saerang, David P. E.; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This research was conducted at PT. Makmur Auto Mandiri Manado, located in Malalayang, Manado city. While the implementation time of this research was carried out in march 2018 until it tas finished. PT. Makmur Auto Mandiri is a company that sells two-wheeled motor vehicles. Thus the company cannot be separated from the imposition of VAT. The company is also subject to income tax 22 for the sale of two-wheeled motor vehicles to the Government which os directly collected by the government treasurer. The purpose of this reseach was to explain how the recording and reporting of VAT and Income Tax Article 22 at PT. Makmur Auto Mandiri. Data sources are taken from tax documents related to research. In this reseach the author uses descriptive method. From the research conducted it can be concluded that PT. Makmur auto Mandiri has carried out tax obligations in accordance with th applicable tax laws. The author still finds some problems in reporting that are not in accordance with the legislation. In addition to evaluation, the author also provides advice that can be considered by the company as input and improvement for the company in terms of better taxation.Keywords: VAT, Income Tax Article 22, Recording and Reporting.Â